Energizing Africa : Achievements and Lessons from the Africa Renewable Energy and Access Program Phase I - World Bank Group (World Bank, Washington, DC, 2016)
Access to energy and economic development go hand in hand. Improving electricity supply and distribution boosts economic growth, creates jobs, and expands the reach of educational and health services. It can also empower women, providing income-generating opportunities and enabling them to spend their time more productively. Unfortunately, more than 589 million people in Sub-Saharan Africa (SSA) live without access to electricity: only 35 percent of the population in SSA has access, compared with 96 and 78 percent in East Asia Pacific and South Asia, respectively. For most Africans, electric power is inaccessible, unaffordable, or unreli¬able. The lack of both quality energy services and access to modern sources of fuel, such as natural gas, liquefied petroleum gas (LPG), diesel, and biofuels, traps them in a world of poverty. The World Bank Group’s engagement in the energy sector is designed to help client countries secure the af¬fordable, reliable, and sustainable energy supply needed to end extreme poverty and promote shared prosperity. The Bank’s approach mirrors the objectives of the Sustainable Energy for All (SE4All) initiative, achieving universal access, accelerating improvements in energy efficiency, and doubling the global share of renewable energy by 2030. The Bank recognizes that each country determines its own path for achieving its energy aspirations: each country’s sustainable energy transition involves a unique mix of opportunities and challenges, prompting different emphases on access, efficiency and renewable.